FACTORS AFFECTING THE SUPPLY CHAIN OF MEDICAL CONSUMABLES - Sekar Arumdani, Intan; Muhammad Fadli Ramadhansyah; Florianus Hans Matheus Mawo; Erlangga Mandala Sakti (Yayasan Nusantara Hasana Berdikari, 2024)
Hospital is a crucial component of the current healthcare system and is in charge of supplying, preserving, and advancing community members' health using various resource. Networks are used to organize the numerous, complex health systems of today. Because of the partners' inconsistent behavior and lack of coordination, these networks are frequently underutilized. Each facility or even by industry or service, optimizes care quality and controls costs locally. A systematic global approach could enhance the general under optimization that emerges from this local concentration. The competition in the current global economy is between supply networks rather than enterprises. The comparison of supply chain performance indicators may last a very long time. This research uses a narrative review approach. There are a total of 23 papers used from databases from Science Direct, ProQuest, Scopus, SpringerLink, Hindawi, Google Scholar, JSTOR, and Emerald Insight. A supply chain's of medical consumables success is influenced by many internal and external factors such as exchange of information, enduring relationships, collaboration, and process integration. Agility becomes increasingly crucial to maintaining cooperation and teamwork, improving patients' experiences every time. Various elements influence the supply chain for medical consumables. Therefore, it is crucial to identify and evaluate the key variables influencing the healthcare supply chain for the medical consumables process and examine the strategies included in this review.